Protocol for randomized controlled trial to evaluate the safety and feasibility of a novel helmet to deliver transcranial light emitting diodes photobiomodulation therapy to patients with Parkinson’s disease - McGee, Claire; Liebert, Ann; Herkes, Geoffrey; Bicknell, Brian; Pang, Vincent; McLachlan, Craig S.; Kiat, Hosen (Frontiers in Neuroscience, 2022)
Introduction Parkinson’s disease (PD) is the second most common, progressive, and debilitating neurodegenerative disease associated with aging and the most common movement disorder. Photobiomodulation (PBMt), the use of non-thermal light for therapeutic purposes using laser or light emitting diodes (LED) is an emerging non-invasive treatment for a diverse range of neurological conditions. The main objectives of this clinical trial are to investigate the feasibility, safety, tolerability, and efficacy of a novel transcranial LED helmet device (the “PDNeuro”) in the alleviation of symptoms of PD. Methods and analysis This is a 24-week, two-arm, triple-blinded randomized placebo-controlled clinical trial of a novel transcranial “PDNeuro” LED Helmet, comparing an active helmet to a sham helmet device. 40 PD participants with Hoehn & Yahr Stage I-III during ON periods will be enrolled and randomly assigned into two groups. Both groups will be monitored weekly for the safety and tolerability of the “PDNeuro” LED Helmet. Clinical signs and symptoms assessed will include mobility, fine motor skills and cognition, with data collected at baseline, 12 weeks, and 24 weeks. Assessment tools include the TUG, UPDRS and MocA all validated for use in PD patients. Patient’s adherence to the device usage and participant drop out will be monitored weekly. At 12 weeks both placebo and treatment groups will crossover and placebo participants offered the treatment. The main indicator for clinical efficacy of the “PDneuro” Helmet is evidence of sustained improvements in motor and non-motor symptoms obtained from participant self-reported changes, carer reporting of changes and objective reassessment by the investigators. The outcomes will assist in a future larger randomised trial design.